Design of Fuzzy Logic Controller for Controlling Physical Parameter - Annigeri, Rekha (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 8 No 3&4 (2021): Journal of Advanced Research in Instrumentation and Control Engineering, 2022)
In this paper the design and development of a fuzzy logic controller for controlling physical parameters is presented. The duty cycle of the DC motor is taken as a prime variant of the system to control the parameters. ATmega16 Microcontroller based system is designed and presented. This technique may find its applications in the systems which need control of physical parameters as a vital factor. How to cite this article: Annigeri R. Design of Fuzzy Logic Controller for Controlling Physical Parameter. J Adv Res Instru Control Engg 2021; 8(3&4): 16-18.